Kajian Endapan Pasir Besi di Daerah Pantai Selatan Kabupaten Ende, Flores, Provinsi Nusa Tenggara Timur - Bambang Nugroho Widi; Kisman Kisman (Buletin Sumber Daya Geologi, 2006)
Iron as One of primary raw material in steel and construction industry, it's presence and potencies in Indonesia have an important role. Genetically, known 3 formation of iron deposits (1) Primary, (2) Lateritic, (3) Secondary/reworking process.Based on the survey conducted in Ende in 2005, the typical of iron deposits in this area is classified into sedimentary iron deposits (due to leaching, transporting, accumulating and depositing in somewhere). The accumulation of magnetite grains suggested is due to by leaching, washing in the long term and occurs intensively, so that produce high magnetite concentration in certain area. The interesting area is spread in four sectors; Rapo Rindu, Bheramari, Ruku Ramba and Ondorea sectors.The result of physical laboratory analysis (in concentrate) show the magnetite degree (MD) is vary from 10% to 50%, whereas from chemical analysis known the highest grade reach 37.10% and lowest grade is around 4.4%. However, the everage grade, in general are from 10 to 25 %.The potential of the deposits is obtained from combination between field work laboratory analysis and for those areas mentioned above the total hypothetics resources is 57.134.358,4 ton (concntrate). It seem the deposits of this area is not economic in mining view because very small (under 100 millions tonnes).